2017
DOI: 10.1007/s40519-017-0456-z
|View full text |Cite
|
Sign up to set email alerts
|

Body weight and mortality in COPD: focus on the obesity paradox

Abstract: Level V: Narrative Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 74 publications
3
106
1
4
Order By: Relevance
“…Obesity is paradoxically associated with a better survival in patients with cardiovascular or renal disease, an observation characterised as the "obesity paradox" [89,90]. This paradox was also observed in COPD patients, as earlier studies reported a relationship between a low BMI and adverse prognosis in terms of mortality as well as rate and duration of hospitalisation [91,92], an association more evident in severe COPD [93]. Similarly, obese patients hospi-talised for acute exacerbation of COPD had a better outcome compared with those of normal weight; for every 1 kg/m 2 increase in BMI there was a 5 % decrease in mortality likelihood [94].…”
Section: Copd and Obesitymentioning
confidence: 90%
“…Obesity is paradoxically associated with a better survival in patients with cardiovascular or renal disease, an observation characterised as the "obesity paradox" [89,90]. This paradox was also observed in COPD patients, as earlier studies reported a relationship between a low BMI and adverse prognosis in terms of mortality as well as rate and duration of hospitalisation [91,92], an association more evident in severe COPD [93]. Similarly, obese patients hospi-talised for acute exacerbation of COPD had a better outcome compared with those of normal weight; for every 1 kg/m 2 increase in BMI there was a 5 % decrease in mortality likelihood [94].…”
Section: Copd and Obesitymentioning
confidence: 90%
“…This can contribute to the degree of weight change after the procedure. Spelta et al [22] raised awareness about the obesity paradox possibly present with COPD. According to their review, several studies have reported obesity to be a protective factor against allcause mortality, including COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, obese patients with COPD survive longer than patients with COPD who are not obese, despite the cardiovascular risk and inflammatory burden associated with obesity. This phenomenon is known as the "obesity paradox" [6][7][8].…”
Section: Introductionmentioning
confidence: 99%